The individual-practice framework: a design tool for understanding consumer behaviour - Piscicelli, Laura; Moreno, Mariale; Cooper, Tim; Fisher, Tom (Springer, 2016)
Design for behaviour change is a growing research field which aims at providing methods and tools to foster pro-environmental and pro-social action through the application of diverse theories, models and approaches from the social sciences. This chapter presents the Individual-Practice Framework, which uniquely combines insights from social psychology and social practice theory, and discusses its possible use as a design tool. The Individual-Practice Framework captures the interrelation between the individual and specific combinations of the ‘material’, ‘meaning’ and ‘competence ’ elements of practices. The framework is proposed here as a design tool for the effective exploration and envisioning of innovative, and conceivably more sustainable, product and service solutions. The paper discusses the advantages of employing the framework as part of the design process, sets preliminary guidelines for practical application and considers possible limitations. It concludes with an assessment of the potential for adoption of the Individual-Practice Framework in participatory design workshops.
Keywords: Consumer behaviour; Individual-practice framework; Participatory design; Social practice theory; Social psychology